A quantum approach to condensed matter physics - Taylor, Philip L (Cambridge University, 2013)
This textbook is an accessible introduction to the theory underlying the many fascinating properties of solids. Assuming only an elementary knowledge of quantum mechanics, it describes the methods by which one can perform calculations and make predictions of some of the many complex phenomena that occur in solids and quantum liquids. The emphasis is on reaching important results by direct and intuitive methods, and avoiding unnecessary mathematical complexity. Designed as a self-contained text that starts at an elementary level and proceeds to more advanced topics, this book is aimed primarily at advanced undergraduate and graduate students in physics, materials science, and electrical engineering. Problem sets are included at the end of each chapter, with solutions available to lecturers. The coverage of some of the most recent developments in condensed matter physics will also appeal to experienced scientists in industry and academia working on electrical properties of materials.' from publisher's description.